The Heroine’s Monomyth: A Study of Buchi Emecheta’s Kehinde (NOBEL: Journal of Literature and Language Teaching, 2023)
Classical and African myths and legends recognize and acknowledge male heroes. The male’s role as protector and keeper of the traditions and cultures of the society accords him the opportunity to embark on heroic journeys. The female’s role as caretaker of the family and the home makes her more docile. Using a close textual analysis on the content of Emecheta’s Kehinde, from the perspective of the Hero’s Journey (Campbell, 1968), the researchers bring to bear the heroic capabilities of females. The paper asserts that Emecheta fashions the protagonist’s journey in a series of departures that help her obtain the ultimate boon. Kehinde’s journey highlights the idea of racial discrimination, patriarchal and cultural shackles, freedom, identity as well as self-love. The paper concludes that the heroine undergoes a non-lineal and unpredictable journey to attain self-discovery, growth, and development.